IMIA’s Publication History - Peterson, H. E.; Hutter, M. (Yearbook of Medical Informatics, 2007)
This article lines out the various publications by which IMIA presents its work and the state-of-the art of health and biomedical informatics.A short history of IMIA and its publications is presented, a reference list completes the view.IMIA looks back on a long and fruitful publication history of more than a hundred publications.Starting from its foundation in 1967, IMIA has continually published the results of its activities and conferences, these publications being one of the most visible proofs of the liveliness and up-to-dateness of the organization and the field.
Keywords: History of Medical Informatics; IMIA publications; International Medical Informatics Association; IMIA